Style, content, and the success of ideas - Boghrati, Reihane; Berger, Jonah; Packard, Grant (Journal of Consumer Psychology, 2023)
AbstractFrom marketers and consumers to leaders and health officials, everyone wants to increase their communications' impact. But why are some communications more impactful? While some argue that content drives success, we suggest that style, or the way ideas are presented, plays an important role. To test style's importance, we examine it in a context where content should be paramount: academic research. While scientists often see writing as a disinterested way to communicate unobstructed truth, a multi‐method investigation indicates that writing style shapes impact. To separate content from style, we focus on a unique class of words linked to style (i.e., function words such as “and,” “the,” and “on”) that are devoid of content. Natural language processing of almost 30,000 articles from a range of disciplines finds that function words explain 4–11% of overall variance explained and 11–27% of language content's impact on citations. Additional analyses examine particular style features that may shape success, and why, highlighting the role of writing simplicity, personal voice, and temporal perspective. Experiments further indicate the causal impact of style. The results suggest ways to boost communication's impact and highlight the value of natural language processing for understanding the success of ideas.